2016
DOI: 10.1038/nature17978
|View full text |Cite
|
Sign up to set email alerts
|

Rocaglates convert DEAD-box protein eIF4A into a sequence-selective translational repressor

Abstract: Rocaglamide A (RocA) typifies a class of protein synthesis inhibitors that selectively kill aneuploid tumor cells and repress translation of specific mRNAs1-4. RocA targets eukaryotic initiation factor 4A (eIF4A), an ATP-dependent DEAD-box RNA helicase; its mRNA selectivity is proposed to reflect highly structured 5′ UTRs that depend strongly on eIF4A-mediated unwinding5. However, rocaglate treatment may not phenocopy the loss of eIF4A activity, as these drugs actually increase the affinity between eIF4A and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
437
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 266 publications
(479 citation statements)
references
References 37 publications
40
437
2
Order By: Relevance
“…These compounds increase the affinity between eIF4A and mRNA and specifically clamp eIF4A onto polypurine sequences in mRNA 5′UTR, thus blocking ribosome subunit scanning and reducing protein expression from transcripts bearing the rocaglamide A–eIF4A target sequence (35). The compound CMLD010509 is a potent and selective translation inhibitor through an eIF4E phosphorylation–independent mechanism (15).…”
Section: Discussionmentioning
confidence: 99%
“…These compounds increase the affinity between eIF4A and mRNA and specifically clamp eIF4A onto polypurine sequences in mRNA 5′UTR, thus blocking ribosome subunit scanning and reducing protein expression from transcripts bearing the rocaglamide A–eIF4A target sequence (35). The compound CMLD010509 is a potent and selective translation inhibitor through an eIF4E phosphorylation–independent mechanism (15).…”
Section: Discussionmentioning
confidence: 99%
“…34,36 To comprehensively test how platelet activation affects translation of specific mRNAs, we performed ribosome profiling on platelets activated with thrombin for 60 minutes at 37°C. To estimate global protein synthesis, we quantified the increase in overall cytosolic ribosome footprints after normalization to footprints derived from mitochondrial ribosomes, 64,65 which are entirely distinct from the cytosolic translational machinery and are continuously synthesized in platelets. 66 These analyses show there is a global increase in ribosome occupancy on cytoplasmic mRNAs, consistent with increased translational output (Figure 1E-F; gray vs blue transcripts).…”
Section: Platelet Mrnas Are Broadly Occupied By Ribosomesmentioning
confidence: 99%
“…Translation initiation could be rescued with recombinant eIF4A after Hippuristanol treatment, showing that Hippuristanol specifically mediates it effect through eIF4A inhibition[19]. mRNAs with a long or complex 5′UTR are most affected by Hippurastinol treatment[78]. …”
Section: Targeting Oncogenic Translation With Dead/h Box Rna Helicmentioning
confidence: 99%
“…indicated that in contrast to Hippurastinol, a complex 5′UTR was only a minor determinant of Rocaglamide A (RocA) efficacy. Instead they found RocA to clamp eIF4A on mRNAs that have short polypurine sequences in their 5′UTR, hereby putting up a roadblock for ribosomal scanning[78] (Figure 4). Unfortunately, RocA was not compared directly to Silvestrol in this study, and it remains to be determined whether the specificity for polypurine mRNA sequences is a feature of all rocaglates.…”
Section: Targeting Oncogenic Translation With Dead/h Box Rna Helicmentioning
confidence: 99%
See 1 more Smart Citation